Effect of medium composition and explant size on embryogenic calli formation of cassava (Manihot esculenta Crantz) local genotypes (Biodiversitas Journal of Biological Diversity, 2006)
Cassava (Manihot esculenta Crantz) is an important tropical crop species used for human consumption, feed and raw material for various industries. Genetic transformation through embryogenic tissues is known as an effective method for cassava genetic improvements. Objective of this study was to obtain a suitable medium and length of explants to induce embryogenic callus on friable embryogenic callus (FEC) as a target for genetic transformation. Immature leaf lobes (1-3 mm, 3-5 mm and larger than 5 mm in length) of local genotypes of cassava (Adira 4. Menti, Iding, Gebang, Rawi and Timtim-29) cultured in vitro were used as explants. The explants were incubated for 2 and 4 weeks on MS (Murashige-Skoog) or GD (Greshooff & Doy) semi solid medium containing 10 mg/L picloram, 6 mg/L NAA supplemented with 4% sucrose and 4 Î¼M CuSO4. Results showed that the highest percentage (100%) of embryogenic calli formation for 4 weeks obtained by culturing Iding of 3-5 mm length on GD semi solid medium, whereas the lowest (33%) one obtained by incubation 5 mmleaf lobe of Timtim-29 on the same medium. The most suitable medium for callus induction was GD, whereas the optimum length of explants was 5 mm or larger. Further study needs to be done to obtain friable embryogenic calli (FEC) by employing different concentration of picloram and varying other critical factors.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Manihot esculenta Crantz, cassava, medium, embryogenic, callus